The role of personality in the approaches to the study of the quality of life for people with limited possibilities - Pelekh, Jurii; Oksentiuk, Natalia (Journal of Education, Health and Sport, 2017)
The article deals with the research of quality of life of people with limited health abilities. First of all, the scientists have focused on the aspect of quality of life which is associated with health. It is obvious that people with limited health abilities need constant health care, rehabilitation and prevention of health consequences of disabilities. This article analyzes the prospects of including a number of phenomena, responsible for positive personal development in the research of quality of life of people with limited health abilities. An alternative to the traditional clinical approach to the study of health and its role in the context of quality of life is the meaning of a subjective factor that mediates the effect of external conditions on subjective well-being and quality of life of people with limited health abilities.